Palladium(ii) and platinum(ii) saccharinate complexes with bis(diphenylphosphino)methane/ethane: synthesis, S-phase arrest and ROS-mediated apoptosis in human colon cancer cells. Issue 33 (31st July 2018) - Icsel, Ceyda; Yilmaz, Veysel T.; Aygun, Muhittin; Cevatemre, Buse; Alper, Pinar; Ulukaya, Engin
Abstract : Highly cytotoxic Pd(ii )/Pt(ii ) complexes of saccharin with diphosphines cause cell arrest at the S phase and the production of excessive ROS, damaging mitochondria and DNA. Abstract : New neutral [M(sac)2 (diphos)] and cationic [M(diphos)2 ](sac)2 complexes, where M = Pd II or Pt II, sac = saccharinate, and diphos = 1, 1-bis(diphenylphosphino)methane (dppm) or 1, 2-bis(diphenylphosphino)ethane (dppe), were synthesized and structurally characterized. The anticancer activity of the complexes was investigated against MCF-7 (breast), A549 (lung), HCT116 (colon), DU145 (prostate) cancer and BEAS-2B (normal bronchial epithelial) cells. Neutral Pt-dppm (2 ) and Pd-dppe complexes (5 ) did not show any biological activity. The cationic Pd-dppe (7 ) complex displayed antiproliferative activity, while the rest of the complexes exhibited potent cytotoxicity compared with cisplatin. The active Pd(ii )/Pt(ii ) complexes were then included in further studies including interaction with DNA/HSA, nuclease activity, cellular uptake and lipophilicity. The potent complexes induced the apoptotic cell death as probed through annexin V positivity and caspase activation. Mechanistic studies on HCT116 cells showed that the complexes cause cell cycle arrest at the DNA synthesis (S) phase and excessive generation of reactive oxygen species (ROS), damaging to both mitochondria and DNA.